Risk assessment of cadmium toxicity on hepatic and renal tissues of rats - Novelli, ELB; Vieira, E. P.; Rodrigues, N. L.; Ribas, B. O. (Academic Press Inc., 1998)
Pollution and industrial practices result in concentrations of metals and other environmental agents that are related to environmental toxicity. A rat bioassay was utilized for the identification of toxic effects of cadmium intake. This demonstrated increased total urinary proteins and increased kidney weights in rats exposed to CdCl2, for 7 days, in drinking water (100 mg/L). Serum creatinine, total and direct bilirubin concentrations and alanine transaminase activity were increased in Cd-exposed rats, indicating renal and hepatic toxicity. It was also observed that lipoperoxide concentrations were increased, while Cu-Zn superoxide dismutase activity was decreased in rats treated with cadmium. This indicated that the renal and hepatic toxicity induced by cadmium involved superoxide radicals. (C) 1998 Academic Press.